Humanitarian Mission of Local History Museums in the Society: Ukraine’s Experience - Babushko, S.; Mankovska, R.; Solovei, M.; Solovei, L (Краєзнавство, 2022)
Local history museums play an important role in modern society. The purpose of the article is to investigate how local history museums in Ukraine perform their mission of humanitarian development of local communities. The article emphasizes the impact of the museum on society’s development. The authors investigated the sites of 160 local history museums in Ukraine and conducted interviews with museum staff. The interview questions included the peculiarities of forming local history museum exposition content, directions of their collaboration and cooperation with local community and effective means of communication with it and the public. As a result, it has been found that the traditional approach is not enough to make the content of the museum exposition a powerful educational and cultural tool where a human is a central figure. Its importance lies in creating favorable socio-cultural environments that shape and develop the personality. New approaches are required based on considering the needs and interests of the visitors. Hence, these new ways of creating humanistic content that can develop a friendly socio-cultural environment were identified. Their main features were outlined and described in the examples. Also, possible disproportions in forming local history museum content in Ukraine were determined. Their elimination will significantly enhance the socio-humanitarian mission of local history museums in society: It was concluded that local history museums actively influence the formation of the socio-humanitarian space of the region, act as intellectual, educational, cultural and communication centers of the community, an effective mechanism of its socio-cultural transformations. Local history museums have the multifunctional potential: scientific-research, educational, cultural-aesthetic, economic. By applying it, the community is capable of socio-humanitarian transformations and productive development. Краєзнавчі музеї відіграють надзвичайно важливу роль у сучасному суспільстві. Метою статті є дослідження того, як краєзнавчі музеї в Україні реалізують функцію гуманітарного розвитку місцевих громад. У статті наголошується на ролі музею у всебічному розвитку суспільства. Автори дослідили сайти 160 краєзнавчих музеїв України та провели бесіди з музейними працівниками щодо особливостей формування експозиційного наповнення краєзнавчих музеїв, напрямів їх співпраці з місцевою громадою та ефективних форм комунікації з нею. У результаті виявилося, що традиційного підходу недостатньо для того, щоб зробити зміст музейної експозиції потужним освітнім і культурним інструментом, де людина є центральною фігурою. Сучасна музейна експозиція потребує інноваційного підходу з урахуванням потреб та зацікавленостей відвідувачів. Таким чином, були визначені нові шляхи створення гуманістичного контенту, який може розвивати дружнє соціокультурне середовище. На прикладах викладено та описано їхні основні особливості. Також визначено можливі диспропорції у формуванні краєзнавчого музейного контенту в Україні. Їх ліквідація розглядається як шлях значного посилення соціогуманітарної місії краєзнавчих музеїв у суспільстві. Узагальнено, що краєзнавчі музеї активно впливають на формування соціогуманітарного простору регіону, виступають інтелектуально-просвітницькими та культурно-комунікаційними центрами громади, дієвим механізмом її соціокультурних перетворень. Застосовуючи поліфункціональний потенціал краєзнавчого музейного закладу: науково-дослідницький, просвітницький, культурно-естетичний, економічний, громада спроможна здійснити соці-ально-гуманітарні трансформації та продуктивно розвиватися.